Pendidikan Anti Bullying: Telaah Hadis dan Pendekatan Psikologi - Bakir, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bullying behavior should not be underestimated because this behavior can have serious repercussions such as impaired mental health, depression, body defects and even the loss of a person’s life due to murder or suicide. Islam strongly prohibits bullying behavior because it is a despicable moral. These prohibitions are not only conveyed in the Qur’an, but also in the Hadiths of the Prophet Muhammad SAW, both of which are life guidelines for Muslims. In addition, bullying also has an impact on the psychic condition of students. This research analyzes in depth the anti-bullying education of hadith and psychological perspectives, focusing on an overview of bullying behavior, psychological impact, and the law of bullying in a Hadith perspective. The type of research used is qualitative, researchers conduct research based on the content of the discussion in the research subject and provide maximum opportunities in an effort to analyze some literature that is directly or indirectly related to the research title with critical nuances from the conceptual side. This research fully uses library research design. The results of this study can be concluded that the Hadith of the Prophet Muhammad SAW. Viewed with the lens of psychology, the hadiths of The Prophet Muhammad SAW do not condone acts of bullying behavior. Not only that, the hadith also teaches anti-bullying values that can be grown in the world of education. The values of anti-bullying perspective of the hadith are: the value of husnuzan, the value of friendship, the value of anti-tajassus, and the value of brotherhood.